Sensor Coordination for Behavior of Search Robot Using Simultaneous Localization and Mapping (SLAM) - Indra Adji Sulistijono; Endah Suryawati N; Eko Henfri B; Ali Husein A; Ananda Verdi S (IPTEK The Journal of Engineering, 2015)
We developed a robot for searching victims for survivors of natural disasters. Almost all robots need to navigate a state in the environment to help people around them, therefore the robot should have performance a mapping system. Thus improve the performance of robots in knowing the obstacles, the position and the direction toward the robot with the task of each sensor is to detect obstacles or objects that exist in the use of ultrasonic sensors to avoid bumping into obstacles, to detect the position and determine the distance of the robot using a rotary sensor encoder and to determine the direction toward, direction and elevation angle of the robot using IMU sensor. Whole of the sensor is set by the microcontroller STM32F407VGT6 that sent data from each sensor to a PC using XBee Pro. Therefore, robot create a mapping with OpenGL on the PC. Mapping system plays an important role for fast and accurate to the destination. We conclude, in the robot SLAM method depends on the precision of the data in the sensor US2 (Right), US4 (Left) and the rotary encoder. The test results of the output data at the right ultrasonic sensor produces error US2 16.9%, 14.6% US4 left ultrasonic and rotary encoder sensor error to 19.45%.